Ang pag-ibig sa bayan ni Andres Bonifacio isang pagtingin sa tulang katipunero - Bonifacio, Andres 1863-1897; Almario, Virgilio S.; Bonifacio, Andres 1863-1897. (Manila UST Publishing House, 2012)
Life of Andres Bonifacio and literary criticism of his poem: Pag-ibig sa tinubuang bayan.
Literary criticism on Pag-ibig sa tinubuang bayan, a poem written by Andres Bonifacio, the father of the Philippine Revolution.
Includes bibliographical references (pages 241-244).
Keywords: Bonifacio, Andres -- 1863-1897.; Philippines -- History -- Revolution, 1896-1898.